The determination of some toxic elements in drinking water by inductively coupled plasma mass spectrometry - Rahman, Md. Mokhlesur; Ansary, R.H.; Azad, Abul Kalam; Yusof, A.M (INSI Publications, 2012)
A method is described for the determination of Cu, Cr, Cd, Pb, Sb, Se and As in drinking water using inductively coupled plasma mass spectrometry (ICP-MS). Samples were taken from water treatment plants of Negeri Sembilan and Melaka. Modified methods were developed for the trace determination of total inorganic arsenic, antimony, chromium, cadmium, selenium, lead, copper and mercury by ICP-MS. Detection limits obtained by ICP-MS for Cr, Cu, As, Se, Cd, Sb and Pb are 250, 66, 59, 48, 8, 85 and 3.28 103 g L-1 respectively. Calibration was accomplished by means of an aqueous calibration curve. The methods were verified by the analysis of quality control standard sample solutions.